Pavlov in Spain - Llavona, Rafael; Bandrés, Javier (The Spanish Journal of Psychology, 2003)
Reflexology has been present throughout Spanish science since the last third of the nineteenth century and its importance can be seen in the works of authors such as Martín Salazar, Ramón y Cajal, Gómez Ocaña, Simarro and Turró. The most important research in Reflexology in Spain takes place a) at the Schools of Neurophysiology and Psychology in Barcelona and Madrid, b) with a group of authors specializing in pathological medicine and c) in the Military’s Health Department. Pavlov’s work was received in Spain with special interest. Fernández-España, who could be considered the “first Spanish Pavlovian,” emphasized Pavlov’s work in a series dedicated to the study of objective psychology which was published between 1914 and 1924. Planelles was the first investigator to develop a program in Pavlovian experimentation, presenting his results in 1935. The Civil War (1936-1939) ended these and many other Spanish projects in psychology. After the war, interest in Reflexology and Pavlov’s theories slowly rose again, first through psychosomatic medicine and then in the 60’s because of the works of such authors as Monserrat-Esteve, Rof Carballo and Colodrón. The progressive inclusion of psychology in the Schools of Philosophy and Arts after 1968 marked the beginning of a new era